(untitled) (Applied Biological Research, 2023)
The present study was aimed to evaluate the phytochemicals present in the ethanolic extract of Achyranthes aspera leaves (EEAA) and identify the bioactive compounds by GC-MS analysis. In vitro antioxidant activity was measured by using DPPH, metal chelating and superoxide radical scavenging assays. The anti-bacterial activity was assayed by disc diffusion method. The results revealed the presence of phenols, flavonoids, and tannins in significant amount in EEAA [372 ± 2 mg GAE g-1, 22.6 ± 1.34 mg CE g-1 and 242 ± 2 mg TAE g-1, respectively. GC-MS analysis revealed the presence of 20 major bioactive compounds with 74.36% total leaf extract, dominated by phytol (10.67%), palmitic acid (6.56%), pseudo-ephedrine (6.06%) and hexacosane (5.76%). EEAA exhibited a maximum DPPH radical scavenging activity of 46.3%. The metal chelation activity in EEAA was 58.8%. The EEAA exhibited a maximum of 46.51% superoxide scavenging activity. In vitro antibacterial activity of EEAA assayed against three human pathogenic bacteria viz., Salmonella typhi, Bacillus subtilisand Escherichia coli. EEAA showed maximum inhibition against B. subtilis (16.33 ± 0.577 mm). The study revealed that A. aspera is a potential source for developing health-oriented products.